The characteristics of latent tuberculosis infection and its influencing factors in hospitalized patients in Suzhou, Jiangsu, China - Yanyang Zhou; Xing Lv; Shuai Zhu; Ping Xu (PLoS ONE, 2025)
Objective China is a country with a high burden of tuberculosis (TB). It is vital to reduce the number of new cases of TB in China. We aimed to examine and investigate the distribution and affecting factors of the latent tuberculosis infection (LTBI) detection rate in hospitalized patients in Suzhou, Jiangsu Province. Methods We analyzed the link between LTBI and patients’ information, disease diagnosis, and blood routine indices of hospitalized patients at the Fifth People’s Hospital in Suzhou from January 1, 2018, to March 31, 2024. Results Results indicated that of the 6692 patients included in the study, 39.05% of them were diagnosed with LTBI. Multivariate analysis revealed that sex, AIDS status, testing time, age, lymphocyte count, and neutrophil count were influencing factors for the detection of LTBI ( p < 0.05). However, hepatitis B, diabetes, hypertension, silicosis and monocyte count did not significantly influence LTBI detection. Conclusion Sex, AIDS status, testing time, age, lymphocyte count, and neutrophil count were influencing factors for the detection of LTBI.